2014
DOI: 10.1111/tbed.12224
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal Variations of Bovine Tuberculosis Incidence in France between 1965 and 2000

Abstract: We analysed the spatiotemporal variations of bovine tuberculosis (bTB) incidence between 1965 and 2000 in France at the department level (95 areas). Using a Bayesian space-time model, we studied the association between the evolution of bTB incidence and changes of cattle population structure and of herd management practices. Several spatiotemporal hierarchical Bayesian models were compared, and the deviance information criterion was used to select the best of them. Southern France remained a high-risk area ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…Our analysis also indicated the presence of temporal heterogeneity ( R 2 = 7.04%) over the 74‐year time frame (1942–2016) represented by the included studies (Table ). While the specific source(s) of this heterogeneity is unclear, contributors may include differences in environmental conditions over time (Humblet et al., ) (Bekara, Azizi, Bénet, & Durand, ), the number of studies within each time interval, animals tested, test operators’ skills/methods and the diagnostic tests themselves. Recent studies have also shown that the quality, origin and source of tuberculin used are variable within tuberculin‐based tests, highlighting a lack of standardization (Bakker et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis also indicated the presence of temporal heterogeneity ( R 2 = 7.04%) over the 74‐year time frame (1942–2016) represented by the included studies (Table ). While the specific source(s) of this heterogeneity is unclear, contributors may include differences in environmental conditions over time (Humblet et al., ) (Bekara, Azizi, Bénet, & Durand, ), the number of studies within each time interval, animals tested, test operators’ skills/methods and the diagnostic tests themselves. Recent studies have also shown that the quality, origin and source of tuberculin used are variable within tuberculin‐based tests, highlighting a lack of standardization (Bakker et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The technique tests whether there is any systematic pattern in the distribution of TB notifications among districts of Zimbabwe as opposed to being randomly distributed. The index ranges from -1 to +1 with a score of zero indicating no clustering while a positive value suggests that the distribution of TB cases in neighbouring districts is more spatially aggregated than a random pattern [ 43 , 44 ]. In contrast, a negative value suggests dispersion of TB cases at the district level.…”
Section: Methodsmentioning
confidence: 99%
“…In France, an officially BT-free member of the European Union (EU), Mycobacterium bovis remains endemic in a few regions of the country ( 5 ). The in-depth genetic study of strains of M. bovis responsible for the persistence of outbreaks revealed several strains with a genotypic profile associated with localization to a specific region ( 6 ).…”
Section: Genome Announcementmentioning
confidence: 99%